2015
DOI: 10.13080/z-a.2015.102.059
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of feasible physiological parameters in drought tolerance evaluation in sorghum: a grey relational analysis

Abstract: Identification and evaluation of drought tolerant germplasm is the primary step for sorghum (Sorghum bicolor L. Moench) breeding and utilization under drought conditions. The objective of this study was to use a grey relational analysis to investigate the role of feasible physiological parameters in evaluating drought tolerance in sorghum. Four sorghum varieties were cultivated in pots with two water treatments, including normal watering (75-80% of the soil moisture capacity) and water deficit (45-50% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Sorghum is considered as a multipurpose crop that provides food, feed, and raw materials for wine, fuel and industrial starch (Wang et al 2015a). Starch is the main component of sorghum grains, which determines the quality of sorghum grains and has an important influence on grain yield, palatability and grain brewing (Xiao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum is considered as a multipurpose crop that provides food, feed, and raw materials for wine, fuel and industrial starch (Wang et al 2015a). Starch is the main component of sorghum grains, which determines the quality of sorghum grains and has an important influence on grain yield, palatability and grain brewing (Xiao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum is mainly planted in arid and semiarid regions of Asia and Africa, and the planting area in these regions accounts for 85% of the worldwide planting area according to 2018 data [27]. However, filling stage is the most important period for yield production, at which drought can lead to severe decline of yield in sorghum [28]. Sorghum can feed at least 5 million people in these areas due to its unique drought adaptability [29][30][31], and sorghum roots play an important role in its drought tolerance [32].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that a higher root activity has been found in the stay green sorghum B35 as compared to non-green-stayed sorghum Sanchisan and is considered as one of the drought-resistant mechanisms under drought conditions [33]. Photosynthetic parameters and osmotic adjustment ability are the principal factors associated with sorghum yield under drought conditions [28]. However, research on root systems is time consuming, expensive, and difficult because plant roots are hidden under the ground.…”
Section: Introductionmentioning
confidence: 99%